THE SALUTOGENIC EFFECTS OF AWE TOLD EXISTENTIALLY. Issue 60 (2022) - Nelson, Rachel
Abstract : Feelings of awe can generate well-being. The typical explanation of this is that an otherwise self-absorbed individual now experiences something so vast that it forges a humble new perspective of self. Self-absorption is replaced by altruistic characteristics that result in a sense of well-being. However, the observations of Martin Heidegger, Jean-Paul Sartre, and Carl Rogers provide an existential framework for understanding the human being in relation to the world and well-being within that framework. And such a framework offers a different perspective on how the experience of awe produces well-being. Existentially understood, incongruence is the anti-thesis of well-being. Incongruence is developed by a hyper-focus on external conditions of worth. Rather than a remedy to self-absorption, the experience of awe offers the remedy of self-absorption, towards congruence. This article will explore key observations by each existentially principled thinker to display this framework in order to comprehend how awe produces well-being within it.